The Effect of Educational Animated Media on Early Reading Skills in Early Childhood at KB Ar-Raudhah - Arinil Haq, Annisa; Ismaniar, Ismaniar (Universitas Negeri Padang, 2026)
This research is motivated by the low early reading ability of early childhood children at KB Ar-Raudhah. This is considered to be one of the reasons because of the lack of interesting learning facilities/media when stimulating children. The study aims to determine the effect of educational animation media on early reading ability in early childhood 3-4 years old at KB Ar-Raudhah Padang. This study used a quasi-experimental method. The study In the 2025/2026 academic year, the population included 13 students at KB Ar-Raudhah. The sample was selected. using the Saturated Sampling Technique with the entire population (100%) as the sample. Data were collected through direct observation of children's early reading activities and abilities, using a development rubric that has been prepared based on early reading ability indicators, which are used in the pretest, treatment and posttest stages. The study analyzed the information using the Wilcoxon test. The findings of the research indicated 1) before being given the action (pretest) the children's initial reading ability was mostly categorized as starting to develop and the children answered more hesitantly, 2) when the action (treatment) was given which was carried out for 3 days of learning which combined visual, audio, and interactive activity elements made the children more interested, active, and easy to understand the letter symbols and their sounds., 3) After the children took the test, their starting reading skills were mostly seen as growing. very well, 4) there was a notable impact observed between the pretest and posttest after the use of educational animation media in the early reading ability of early childhood children because the Wilcoxon test was 0.001 <0.05.